158k views
3 votes
Which equation is equivalent to y - 6 = -12(x+4)?

Which equation is equivalent to y - 6 = -12(x+4)?-example-1

2 Answers

2 votes

Answer:


x = ( - 1)/(12) y + ( - 7)/(2) \\ c. \: y = - 12x - 42

Explanation:


1. \: - 12x - 48 = y - 6 \\ 2. \: - 12x = y + 42 \\ 3. \: (12x)/( - 12) = (y + 42)/( - 12) \\ x = ( - 1)/(12) y + ( - 7)/(2)

User AleFranz
by
5.6k points
4 votes

Answer:

The answer is y = -12x - 42

Explanation:

First distribute -12 into the paranthesis.

y - 6 = -12x - 48

Then add 6 to both sides.

y = -12x - 42

That's your final answer. I hope this helps love! :)

User Zwep
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.